Paleosols of the Permian-Triassic: proxies for rainfall, climate change and major changes in terrestrial tetrapod diversity. (29th November 2017) - Tabor, Neil J.; Myers, Timothy S.; Sidor, Christian A.; Smith, Roger M. H.; Nesbitt, Sterling J.; Angielczyk, Kenneth
ABSTRACT: Stable carbon isotope analysis of coexisting soil calcite and organic matter sampled from modern, California soil profiles representing 18 different U.S. Department of Agriculture (USDA) official soil series yields 51 paired calcite–organic matter δ 13 C values (Δ 13 Ccc-om values). These paired values correspond to atmospheric pCO2 estimates ranging from less than ∼100 to 2200 ppmV using standard assumed soil pCO2 concentrations at temperatures spanning the typical range of modern soil calcite crystallization. Nevertheless, there is a strong negative correlation of Δ 13 Ccc-om values with mean annual precipitation (MAP) among these modern sites, offering a potential means to estimate paleo-MAP values from calcite and associated, occluded organic matter in paleosols. One hundred and twenty-five Δ 13 Ccc-om values from lower Permian–lower Middle Triassic paleosol profiles in the southwestern U.S.A., northwestern China, and Africa are presented as a proxy for paleorainfall over ∼85° of paleolatitude. The results indicate substantial spatiotemporal variation in MAP and appear to reflect the development and strengthening of global megamonsoonal atmospheric circulation associated with assembly of the supercontinent Pangea. The data also indicate extremely low rainfall values in regions with endemic tetrapod fossil assemblages, suggesting that climate change was a principal driver of biogeography, biodiversity, and evolution of tetrapod faunas across continental landscapes during Permo-Triassic time. Citation for this article: Tabor, N. J., C. A. Sidor, R. M. H. Smith, S. J. Nesbitt, and K. Angielczyk. 2018. Paleosols of the Permian-Triassic: proxies for rainfall, climate change, and major changes in terrestrial tetrapod diversity; pp. 240–253 in C. A. Sidor and S. J. Nesbitt (eds.), Vertebrate and Climatic Evolution in the Triassic Rift Basins of Tanzania and Zambia. Society of Vertebrate Paleontology Memoir 17. Journal of Vertebrate Paleontology 37(6, Supplement).